PENGEMBANGAN BAHAN AJAR LISTRIK MAGNET BERBASIS ANDROID DI PROGRAM STUDI PENDIDIKAN FISIKA IKIP PGRI PONTIANAK - Matsun, Matsun; Ramadhani, Dochi; Lestari, Isnania (Jurnal Pendidikan Matematika dan IPA, 2018)
This study aims to: (1) develop android based Â magnet learning media in Physics Education Study Program; (2) to know the feasibility of learning media of Magnet Power based on androiddi of Physics Education Program. This research is a research and development (R & D) which refers to the model proposed by Thiagarajan by using 4-D model (Four-D Models) which consists of four stages, namely: define, design stage, development (develop), and dissemination stage (disseminate). The feasibility of android-based learning media is validated by material experts and media experts. Based on the result of data analysis, it is concluded that (1) the learning media of Android-based Magnet Electricity in Physics Education Study Program successfully developed with 4-D (Four-D Models) model that is define, design, develop, and disseminate. (2) learning media of Magnet Power based on android in Physics Education Study Program developed feasible to use with very good Â category.Keywords: Learning Media, Magnet Electricity, Android.